Whole mitochondrial genome sequencing and phylogenetic analysis of Gangetic mystus (Mystus cavasius) - Suvra Roy; Pranaya Kumar Parida; V. L. Ramya; Vikash Kumar; Dibakar Bhakta; Bijay Kumar Behera; Basanta Kumar Das (Mitochondrial DNA. Part B. Resources)
Mystus cavasius, known as Gangetic mystus, is a freshwater indigenous catfish. The present study represents the first-ever complete mitochondrial genome sequencing of M. cavasius. The whole mitochondrial genome size is 16,554 bp (GenBank accession number OR018997). The mitogenome organization consists of total 37 genes, with 13 protein-coding genes, two rRNA, 22 tRNAs, and a D-loop regulatory region. Among these, 28 genes are coded on the heavy strand, while eight tRNA genes and ND6 are encoded separately. Phylogenetic analysis reveals that M. cavasius clusters with other Mystus species and bagrid catfishes. This work contributes valuable insights into structural characterization and phylogenetic relationships.